Wage change in the lithuanian labour market - Laura Žiogelytė (Mokslas: Lietuvos Ateitis, 2010)
In a market, the labour force of the population can be sold and bought. The wage is the price or the monetary value of the labour force. The wage rate depends on the key internal and external factors. In a market economy, remuneration for work becomes the object of negotiation between the employer and the employee. In order to legally implement this negotiation, we need to describe the term of the wage, wage systems, wage structure, functions and other issues. The article deals with the theoretical issues relating to wages: the concept of the wage, the main function of wages, the factors influencing the wage rate are analysed and systematised. The article analyses net wages and gross wages and other factors influencing the Lithuanian labour market.